Penerapan Digital Marketing pada UMKM Artsya Laundry di Kota Batam - Suprapto, Yandi; Lindawati (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Artsya Laundry MSME is a business operating in the service sector that offers washing and scrubbing clothes and the like, which was established in the city of Batam and started operating from 2021 until now. With problems, such as the lack of active digital marketing in introducing MSMEs so that they are more widely known by the people of Batam City and the lack of promotions carried out to increase customer loyalty, this has a big impact on MSMEs. The aim of this activity is that by designing a marketing strategy using digital marketing and carrying out promotions, it is hoped that it can introduce MSMEs so that they are better known by many people, and can also attract the attention of the wider community of Batam city and can also maintain the loyalty of old and new customers. The methods used are observation, interviews and documentation. By carrying out this service, Artsya Laundry UMKM's social media is slowly increasing in number of followers over time, which means that by using ads on social media, MSMEs are becoming known to more people, and MSME orders are continuously increasing, resulting in additional employees.